Strategi Budaya Sekolah 7S dalam Internalisasi Nilai Islam pada Siswa SMP Swasta Kota Yogyakarta - Indriani Ika Puspitasari; Djamaluddin Prawironegoro (Universitas Ahmad Dahlan, 2026)
Internalization of Islamic values ​​in schools still faces challenges in consistently shaping students' character through a sustainable school culture. This condition indicates the need for habituation strategies that can integrate Islamic values ​​into students' daily activities at school. This study aims to describe the implementation of the 7S strategy (smile, greeting, politeness, courtesy, patience, and gratitude) in the internalization of Islamic values ​​and its impact on student character formation. The study used a descriptive qualitative approach with research subjects consisting of the principal, 2 teachers, and 3 students. Data were collected through observation, interviews, and documentation using instruments in the form of observation guidelines, interview guidelines, and documentation of school activities. Data analysis used the interactive model of Miles, Huberman, and Saldana, which includes data condensation, data presentation, and drawing conclusions. The results indicate that the 7S strategy is implemented in an integrated manner in learning, school culture, and social interactions, thereby fostering religious attitudes, discipline, mutual respect, responsibility, and harmonious social relationships. This study indicates that the 7S strategy is effective in strengthening Islamic school culture and developing students' character sustainably.